2014
DOI: 10.1002/jso.23676
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peritoneal CEA levels following colorectal cancer surgery

Abstract: Postoperative pCEA levels may be significantly elevated following a curative resection for CRC. Its significance within patient's prognostic evaluation remains to be studied. Inclusion of patient's follow-up data may reveal the significance of elevated pCEA levels following CRC resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Several studies have demonstrated a significant elevation in CEA levels within the postoperative peritoneal drainage fluid of patients with gastrointestinal tumours. This surge in CEA levels has been closely correlated with tumour invasion depth, lymph node metastasis, and clinical staging, thereby serving as a potential prognostic indicator [ 18 , 19 ]. Wei et al inferred that laparoscopic radical gastrectomy does not increase the shedding of gastric cancer cells by comparing CEA levels in the peritoneal lavage fluid [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a significant elevation in CEA levels within the postoperative peritoneal drainage fluid of patients with gastrointestinal tumours. This surge in CEA levels has been closely correlated with tumour invasion depth, lymph node metastasis, and clinical staging, thereby serving as a potential prognostic indicator [ 18 , 19 ]. Wei et al inferred that laparoscopic radical gastrectomy does not increase the shedding of gastric cancer cells by comparing CEA levels in the peritoneal lavage fluid [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the progression of CRC is dependent on both local and systemic inflammatory responses, these indices have been used to develop CRC-specialized screening markers or scoring systems, namely, the single neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR) (13)(14)(15), CRC tumor markers (CA19-9 and CEA), modified Glasgow Prognostic Score (mGPS, albumin, and C-reactive protein in serum) (16,17), systemic inflammation score (SIS, serum albumin, and LMR) (18), and fecal-based testing (19,20). However, the lack of sensitivity of these methods makes early diagnosis of CRC challenging (21). Therefore, the development of a more effective, noninvasive, and high-throughput method for disease-progress surveillance is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CEA is considered as a tumor marker in clinical findings. 18,19) In medicine, the CEA test contributes to the early and clearly identification of etiologies so that appropriate and effective preventive and curative measures can be taken timely.…”
Section: Introductionmentioning
confidence: 99%